Fear Behaviour, Ease of Capture and Performance Traits of Growing Meat Type Chickens - Ghareeb, K.; Bohm, J. (International Journal of Poultry Science, 2008)
The damaging effects of fear on a number of performance indicators in poultry and other farm animals are becoming increasingly recognized. Indeed, there is a growing evidence for the negative association between growth and fearfulness (an underlying behavioural characteristic). The present study examined the putative relationship between fearfulness and body weight in growing broiler chickens at age of harvesting (35-42 days old). As fearfulness is particularly influential trait in domesticated species, the finding that such trait respond to artificial selection may have important implications for poultry welfare and performance. However, it is not known how fearfulness and growth influenced human-animal interactions. The present experiment investigated also the influence of fearfulness and live body weight of broilers on the ease with which birds could be caught and handled. Furthermore, due to increasing the price of cereal grains in the last two years, it become necessary to evaluate the body weight gain and feed conversion efficiency at earlier age of growing period (5 wk) and comparing data from normal harvesting age in Europe (6 wk). The results showed a significant correlation between fearfulness and human animal interactions. Indeed, the duration of tonic immobility was higher for the birds captured first (rank 1) compared with birds captured afterwards (rank 2). This indicates that birds captured firstly were more fearful than birds afterwards. Moreover, the ease of capture rank was negatively correlated with the duration of tonic immobility at week 5 (-.364) and with the number of tonic immobility inductions at week 6 (-.238). This suggests that more fearful birds (birds had longer tonic immobility duration and higher number of tonic immobility inductions) were captured more easily than less fearful ones. Interestingly, body weight had a significantly negative correlation with the number of inductions required to induce tonic immobility reaction at week 6 (-.415, p < 0.05). This may indicate that heavier birds were less fearful (required less number of induction trials to induce tonic immobility) than lighter birds. Furthermore, the body weight gain was higher at week 5 (628±29g) than at week 6 (585±40g). The feed intake and feed conversion rate were lower at week 5 (985g and 1.57, respectively) than at week 6 (1075g and 1.84, respectively). This indicates that harvesting of growing broilers at week 5 is better for the broiler producers in the term of the economic costs especially after the elevation of prices of cereal grains during the last two years. Finally, there was no significant effect of age on either the tonic immobility duration or number of inductions required to induce tonic immobility reaction (p > 0.05).